Inhibition of RORγT Skews TCRα Gene Rearrangement and Limits T Cell Repertoire Diversity - Guo, Yanxia; MacIsaac, Kenzie D.; Chen, Yi; Miller, Richard J.; Jain, Renu; Joyce-Shaikh, Barbara; Ferguson, Heidi; Wang, I-Ming; Cristescu, Razvan; Mudgett, John; Engstrom, Laura; Piers, Kyle J.; et al. (Cell reports (Cambridge), 2016)
Recent studies have elucidated the molecular mechanism of RORγT transcriptional regulation of Th17 differentiation and function. RORγT was initially identified as a transcription factor required for thymopoiesis by maintaining survival of CD4+CD8+ (DP) thymocytes. While RORγ antagonists are currently being developed to treat autoimmunity, it remains unclear how RORγT inhibition may impact thymocyte development. In this study, we show that in addition to regulating DP thymocytes survival, RORγT also controls genes that regulate thymocyte migration, proliferation, and T cell receptor (TCR)α selection. Strikingly, pharmacological inhibition of RORγ skews TCRα gene rearrangement, limits T cell repertoire diversity, and inhibits development of autoimmune encephalomyelitis. Thus, targeting RORγT not only inhibits Th17 cell development and function but also fundamentally alters thymic-emigrant recognition of self and foreign antigens. The analysis of RORγ inhibitors has allowed us to gain a broader perspective of the diverse function of RORγT and its impact on T cell biology. [Display omitted] •RORγ antagonist treatment recapitulates Rorc-deletion-induced DP thymocyte apoptosis•RORγ regulates genes that control TCRα selection, thymocyte migration, and apoptosis•RORγT inhibition skews TCRα usage and limits T cell repertoire diversity•RORγ antagonist reduces MOG-tetramer+ TCR precursor frequency and EAE Guo et al. find that small-molecule RORγT antagonist treatment induces CD4+CD8+ thymocyte apoptosis, skews the T cell repertoire, prevents autoreactive T cell development, and delays autoimmune EAE progression. This work underscores the risk versus benefit of targeting RORγT in clinical testing of RORγT inhibitors.